Survival to Adulthood and the Growth Drag of Pollution - Andreas Schaefer (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
Environmental pollution adversely affects children's probability to survive to adulthood, reduces thus parental expenditures on child quality and increases the number of births necessary to achieve a desired family size. We argue that this mechanism will be intensified by economic inequality because wealthier households live in cleaner areas. This is the key mechanism through which environmental conditions may impose a growth drag on the economy. Moreover, the adverse effect of inequality and pollution on children's health may be amplified, if the population group that is least affected decides about tax-financed abatement measures. Our theory provides a candidate explanation for (1) the observed positive correlation between inequality and the concentration of pollutants at the local level, and (2) the humpshaped evolution of child mortality ratios between cleaner and more polluted areas during the course of economic development.
Keywords: O10; Q50; I10; 330; Endogenous Growth; Endogenous Fertility; Inequality; Mortality; Pollution; Umweltbelastung; Wirkungsanalyse; Fertilität; Kindersterblichkeit; Kinder; Gesundheit; Endogenes Wachstumsmodell; Overlapping Generations